Terkaman Konsumsi Gadget sebagai Produk Globalisasi Melawan Degradasi Kebudayaan Nasional - Aisyah Syamsuddin (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2021)
This study aims to discuss the culture and culture that are beginning to be eroded by gadgets as a product of the current development of globalization. The deterioration of culture is caused by addiction to the use of gadgets which at present, and has evolved into a very interesting item, one interesting thing is social media, the habit has developed into one of the phenomena that is continuously carried out all the time which has now become a habit. The method in this research is Systematic Literature Reviews (SLR), which is a synthesis of systematic, clear, comprehensive literature studies by identifying, analyzing, evaluating through collecting existing data with a search method that involves a critical review process in selecting. studies. In this study, the researchers conducted data searches through websites, journal portals and some data from books. The result of this research is the occurrence of a moral crisis due to the impact of globalization. One of the developments in the flow of globalization towards culture is that there is westernization or a westernized culture which is the cause of moral crisis and eroding local culture.